Ultrasound Examination of the Ligament Complex Within the Medial Aspect of the Ankle and Foot - Martinez-Franco, Alfonso; Gijón-Noguerón, Gabriel; Franco-Romero, Alberto; Tejero, Sergio; Torróntegui-Duarte, Marcelino; Jiménez-Díaz, Fernando (W.B. Saunders, 2022)
To properly diagnose and treat injuries to the ankle or foot, the physician must have good anatomical knowledge of the ligaments involved. The bundles can be distinguished and identified by ultrasound examination of the medial aspect, but this may be a challenging task. In the present illustrated study, we discuss how a detailed ultrasound examination can be made of the different ligaments within the medial aspect of the ankle and foot.
Keywords: Ligamentos; anterior tibiotalar ligament; deltoid ligament; medial talocalcaneal ligament